استخلاف الإنسان في الأرض بوصفه مقصداً عاماً للقرآن والشريعة والحضارة - عبد السلام محمد الأحمر (International Institute of Islamic Thought, 2017)
يحاول البحث التوصل إلى اقتراح مقصد عام مؤطر لجميع المقاصد القرآنية، وقادر على تجلية نسقية الخطاب القرآني، وذلك استناداً إلى المقصد الأساس لله تعالى من خلق الإنسان حراً مسؤولاً عن نفسه ووجوده الدنيوي والأخروي. ويُبيِّن البحث أن هذا المقصد الأساس هو استخلاف الله الإنسان في الأرض، ثم يسعى إلى بيان مدى ملاءمة المقصد الاستخلافي لتأطير المقاصد الإلهية الشاملة، ولا سيما مقاصد القرآن والشريعة والحضارة، فضلاً عن إبراز مدى قدرة الاستخلاف على استيعاب مختلف الاتجاهات الفكرية الإنسانية، وتحفيز الإنجاز العمراني الإسلامي. This paper tries to identify a general intent that encompasses all the Qur'anic intents, and demonstrates a systematic discourse of the Gracious Qur'an. This attempt is based on what we think Allah's purpose of creating a free and responsible Man in his existence on earth and the hereafter. The paper shows that this general intent is the Vicegerency of Man on earth, and that this intent is a frame of reference to all intents of the Gracious Qur'an, the Shari'a and civilization. Furthermore the paper shows that the concept of Vicegerency would highlight the extent to which it accommodates different human intellectual trends, and stimulates Islamic civilizational accomplishments.